The gamma-glutamyl transferase to platelet ratio and the FIB-4 score are noninvasive markers to determine the severity of liver fibrosis in chronic hepatitis B infection. Issue 3 (3rd July 2018) - Lee, J; Kim, MY; Kang, SH; Kim, J; Uh, Y; Yoon, KJ; Kim, HS
Abstract: Objective: Noninvasive liver fibrosis evaluation is an important issue in chronic hepatitis B infection, and may be assessed using transient elastography (Fibroscan) or with blood markers. We compared the value of Fibroscan with that of a panel of routine serum markers. Materials and methods: We recruited 278 chronic hepatitis B patients who underwent Fibroscan and HBV DNA testing. Fibroscan assessments were made, and blood taken for the measurement of the gamma-glutamyl transferase (GGT) to platelet ratio (GPR), platelet count, aspartate aminotransaminase (AST), alanine aminotransaminase (ALT), international normalised ratio (INR), total cholesterol, trigylcerides, bilirubin, mean platelet volume (MPV), AST to platelet ratio index (APRI) and neutrophil to lymphocyte ratio. Results: A fibrosis index based on four factors (FIB-4) and GPR were higher and platelets were lower in mild liver fibrosis than in non-liver fibrosis. GGT, AST, ALT, INR, MPV, APRI, FIB-4, GPR, and NLR were higher, and platelet and cholesterol were lower in severe liver fibrosis than in mild liver fibrosis. Elevated GPR (Odds ratio 95% CI 9.1 [1.66–50.0] p  = 0.011) and FIB-4 (2.3 [1.2–4.2], p  = 0.01) were associated with greater risk of liver fibrosis. The areas under the curve (AUC) were for GPR 0.84 at a cut-off of 0.299 and for FIB-4 0.82 at cut-off 1.571. Conclusions: FIB-4 and GPR may be useful blood markers for evaluating the severity of liver fibrosis in chronic hepatitis B patients. Further prospective study is required to validate these noninvasive blood markers in a clinical practice.